Islamic Marketing Ethics at Gelugur Market Rantauprapat - Rizki Syahputra (CV. AFDIFAL MAJU BERKAH, 2022)
Muslim business efforts will progress and develop rapidly because they always get the blessing of Allah SWT in the world and in the hereafter. Islamic trade ethics guarantees that both traders and buyers will benefit from each other. This study uses a type of field research, in which the data sources used are primary and secondary data, sources of data relating to research directly which include documents and interviews directly to traders in the Gelugur Rantauprapat Market. Data collection methods used were interviews, documentation and observation. While the analysis used by using qualitative analysis and descriptive analysis. Based on interviews with several consumers and traders of Gelugur Rantauprapat Market, marketing ethics applied by every trader, especially traders in Gelugur RantauprapatMarket, is not just marketing merchandise but applies the principles of ethicsmarketing, including 1). Spiritual Personality. 2).Justice in Business, 3). Services, 4). The accuracy of the promise ,. 5). Honesty